Intramolecular photochemical [2 + 1]-cycloadditions of nucleophilic siloxy carbenes. Issue 11 (2nd March 2022) - Bunyamin, Amanda; Hua, Carol; Polyzos, Anastasios; Priebbenow, Daniel L.
Abstract : Visible light induced singlet nucleophilic carbenes undergo rapid [2 + 1]-cycloaddition with tethered olefins to afford unique bicyclo[3.1.0]hexane and bicyclo[4.1.0]heptane scaffolds. Abstract : Visible light induced singlet nucleophilic carbenes undergo rapid [2 + 1]-cycloaddition with tethered olefins to afford unique bicyclo[3.1.0]hexane and bicyclo[4.1.0]heptane scaffolds. This cyclopropanation process requires only visible light irradiation to proceed, circumventing the use of exogenous (photo)catalysts, sensitisers or additives and showcases a vastly underexplored mode of reactivity for nucleophilic carbenes in chemical synthesis. The discovery of additional transformations including a cyclopropanation/retro-Michael/Michael cascade process to afford chromanones and a photochemical C–H insertion reaction are also described.